Review Artikel Pengembangan Penyalutan Tablet Terhadap Kualitas dan Mekanisme Obat: Review Artikel Pengembangan Penyalutan Tablet Terhadap Kualitas dan Mekanisme Obat - Pratama, Reza; Rodinah, Ina; Bokotei, Martini; willis, Hawa; Oktapiani, Selvia; Hostati, Febri; Pahlevi, Muhammad Reza (LP4M STIKes Karsa Husada Garut, 2024)
Introduction: Tablets are the most popular dosage form to be given to patients, with most of the tablets produced having a thin layer of film coating. Method: used in studying the development of tablets with coating is Systematic Literature Review (SLR). Result: There are various methods to reduce product failure and development costs. Real-time assessment of coating quality is essential, especially in automated production. Therefore, the implementation of PAT is the latest trend for more effective monitoring and control of pharmaceutical unit operations. In addition to PAT, computational modeling is also actively used to aid in understanding, prediction, and problem-solving in film coating operations. Conclusion. Based on the journal review, it can be concluded that coating can be done for various purposes, ranging from improving the physical properties of tablets to improving the stability of tablets in the tablet manufacturing process. Keywords: tablet coating, tablet development, coating development, tablet coating development.